Historia y cine - UROZ, José ed. (UNIVERSIDAD DE ALICANTE, 1999)
Otros autores:ROLDAN HERVAZ, José Manuel; PRIETO, Alberto; ALVAR, Jaime; FATAS, Guillermo; GARCIA MORENO, Luis A.; TEJA, Ramón; BARRIO BARRIO, Juan Antonio; HUGHES, Brian; GIMENEZ, Enrique; ROMA, Armando Alberola; MARTINEZ GOMIS, Mario; LA PARRA LOPEZ, Emilio; FORNER MUÑOZ, Salvador; DOPAZO, Antonio